Understanding farmers’ indicators in climate-smart agriculture prioritization in Nwoya District, Northern Uganda - Shikuku, Kelvin Mashisia; Mwongera, Caroline; Winowiecki, Leigh Ann; Twyman, Jennifer; Atibo, Christopher; Läderach, Peter R.D. (International Center for Tropical Agriculture, 2015)
The purpose of this study was to understand the indicators that farmers use to prioritize agricultural innovations, in general, and climate-smart agriculture (CSA), in particular.